Impacts of RSCVD Project in Türkiye ILL Systems - Ekingen Flores Mamondi, Filiz (ADA University Library, 2024)
The RSCVD initiative was created by members of the IFLA Document Delivery and Resource Sharing (DDRS) Committee during the pandemic, with the aim of supporting libraries that faced challenges in accessing collections due to lockdowns. Originally launched in response to the pandemic, the project continues to be supported by university libraries in Turkey and offers free article requests through the voluntary efforts of library professionals. This initiative facilitates resource sharing and ensures ongoing access to vital academic materials. During the pandemic, there was a strong push to introduce the RSCVD project to our colleagues and encourage its use. Several leading universities in Türkiye, including Bahçeşehir University, Boğaziçi University, Hacettepe University, Işık University, İstanbul Bilgi University, Koç University, MEF University, Özyeğin University, and Sabancı University, all contributed to the project. They played an important role in distributing publications to their users, ensuring continued access to resources." The aim of this study is to introduce the resource sharing systems in our country and to assess the extent to which the RSCVD project has been heard of and used in Türkiye after the pandemic through a survey study.
Keywords: RSCVD; Resource sharing; IFLA DDRS; Academic materials